Synthesis of Esters Containing Cinnamoyl Motif with Potential Larvicide Action: A Computational, Ecotoxicity and in Vitro Cytotoxicity Assessments. Issue 11 (20th October 2022) - dos Santos Correia, Paulo Ricardo; de Carvalho, Cenira Monteiro; da Silva Cunha, Cristhyan Rychard; da Silva, Rafael Antonio Santos; de Oliveira Lima, Monaly; França, Saraliny Bezerra; de Oliveira Barreto, Emiliano; Tonholo, Josealdo; da Paz Lima, Dimas José
Abstract: An increasing morbidity and mortality rate has been related to arboviruses transmitted by Aedes aegypti . Compounds with cinnamoyl moiety represent an alternative against mosquitos, considering their larvicidal activity. This study aimed to assess the larvicidal activity of cinnamic ester derivates against Aedes aegypti larvae, along with evaluating their toxicity effect to assess its safety as a larvicide. Ethyl cinnamate demonstrated larvicidal activity (LC50 =48.59 μg/mL). Morphological changes in larvae were detected, as a degenerative response in the thorax. Through molecular docking, the molecular binding mode between 3b, 3c, and acetylcholinesterase showed strong hydrogen bond interactions. Preliminary in vitro cell viability revealed the non‐cytotoxicity of 3c . Ecotoxicity results indicated a sensitivity of Artemia salina to cinnamic esters. The phytotoxicity bioassays show potential for cinnamic compounds to enhance germination and root development. These findings suggest that compound 3c is more suitable as a larvicide since it demonstrated low toxicity. Abstract :